Peningkatan Kewaspadaan Terhadap Infeksi Saluran Pernafasan Akut Pasca Covid-19 - Machrumnizar Machrumnizar; Rina K. Kusumaratna; Hendra Kurniawan; Suriyani Tan (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The COVID-19 pandemic has become one of the most significant events in history, impacting the global health system, as reported by the World Health Statistics by the World Health Organization (WHO) in 2020. While its focus is on COVID-19, the pandemic has underscored the importance of respiratory health in everyday life. Throughout the pandemic, communities worldwide have learned more about the significance of maintaining a healthy respiratory system. However, with the end of the acute phase of the pandemic, attention to other acute respiratory infections (ARI) may have decreased. Diseases such as tuberculosis, influenza, pneumonia, bronchitis, and others remain serious threats to public health. Therefore, this Community Service (PKM) aims to provide comprehensive education to the public, reminding them of the importance of maintaining respiratory health, recognizing ARI symptoms, and implementing appropriate preventive measures. This community service activity is expected to provide a deeper understanding of ARI and explain how simple actions can help prevent ARI, enhancing knowledge and awareness of respiratory infections.